Analisis Kualitatif Rhodamin B pada Kue Ku yang Beredar di Pasar Tradisional Kabupaten Sleman Yogyakarta - Siti Fatimah; Dian Wuri Astuti; Suryani Dwi Lestari (Journal of Health (JoH), 2016)
Background : A food additive used to obtain food products that taste delicious, attractive, durable, easy in its distribution. Food additives that are often used in society is dye. Many fraud by producers to attract consumers such as the use of non-food grade dyes or food grade with doses exceeding the rules. Rhodamine B is a dangerous synthetic dyes are often added to foods as a dye. Kue Ku is made from a mixture of potatoes, coconut milk, glutinous rice flour, salt, sugar and red dye. The red color on my cake due to the addition of the dye rhodamine B. The use of rhodamine B can cause negative impacts on the health of consumers, thus attracting researchers to examine the presence of rhodamine B dye on my cake circulating in traditional markets Sleman, Yogyakarta. Method : The method is a descriptive study with the aim to describe or illustrate the existence of rhodamine B on kue Ku samples circulating in traditional markets Sleman, Yogyakarta. The method used for laboratory test is by thin-layer chromatography. Results : In this study showed 15,38% of Kue Ku samples have been investigated positive for rhodamine B. Conclusion : There dye rhodamine B on Kue Ku circulating in traditional markets Sleman, Yogyakarta.